Analisis Dan Implementasi Load Balancing Pada Web Server Dengan Algoritme Shortest Delay Pada Software Defined Network - Lucky Ronny Chandra Negara; Widhi Yahya; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Software defined network separation between network architecture is a control plane and data plane. One example of a program that can be implemented on SDN is load balancing. Load balancing is distributing server load to multiple servers. There are several types of load balancing algorithms one is round-robin. When one of the servers was given a huge burden automatically delay getting bigger so in the round-robin will continue through it, this is due to the round-robin divides the load to the server silkular. On the study of load balancing algorithm used is the shortest delay. Shortest delay algorithm to allocate a connection to the server with the lowest delay. This testing to measure performance include throughput, connection rate and reply time. The data obtained using the algorithm of shortest delay compared to the round robin with the same test parameter. Load balancing system with the shortest delay algorithm on testing throughput gives the average connections per second that is 3800.45 KB/s compared to the round robin algorithm that is 3724.26 KB/s. On algorithms shortest delay value the average on a test connection rate that is 3.78 conn/s compared with the average value of round robin algorithm that is 3.70 conn/s. results for reply time on algorithms shortest delay superior to the average value of 177.46 ms compared to the value of the average round robin 266.22 ms.